(untitled) (American Journal of Energy and Natural Resources, 2024)
The main objective of this study is to compare the characteristics obtained from the laboratory with the characteristics obtained from well logs and experimental correlations and determine the percentage of error in each method. Core Analysis of reservoir rock is operation of conducting laboratory tests on the core samples to determine their physical and petro physical properties. The Rock sample is first cleaned to be ready for laboratory test then it is used to obtain parameters of rock properties. Well logging is the practice of making a detailed record of the geologic formations penetrated by the well. The log may be either geological logs or geophysical logs in geothermal. Techlog Software is one of the most valuable formation evaluation software’s used by geologist and reservoir engineers. It is routinely used to evaluate well and field performance, and reservoir characteristics. After evaluating the results, the crude sample was characterized by using hydraulic unit technique its performing to estimate the units inside the reservoir and establish the correlations to estimate the permeability for each unit. The New Correlations can be used to evaluate the permeability nearby wells. In this study Four wells were selected from different locations in 103A which are A7, A11, A16, and A21 They are used to estimate the petro physical properties of the reservoir by both core analysis and well logging interpretation; the petro physical properties were evaluated like porosity, permeability, and water saturation.